the PENGARUH BRAND IMAGE BRAND TRUST DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE (Survey Pada Pengguna Shopee Di Kota Klaten) - erika novianda .putri@unisri.ac.id; Retno Susanti; Lamidi Lamidi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2022)
The goal of this research wass to assess the relevance of the brand image, brand trust, and pricing on Purchase Decision. This form of reseach is survey. Census on Shopee users in Klaten city. The population of this research are those who reside in Klaten who have shopeed online at the Shopee marketplace, the number of which is not known with absolutely. The research sample was 100 respondent. Data collecting strategies employing a questionnaire. The data analysis approach ussed multiple linier regression analysis, t test, F test and coefficient of determination. The findings demonstrated that the brand image has a substantial influence on buying choice at Shopee marketplace in Klaten City. Brand trust has no major influence on buying choice at Shopee marketplace in Klaten City. Price has a huge influence on buying choice at Shopee marketplace in Klaten City.